What Makes the Implementation of Clinical Information Systems Difficult in Nursing Homes?: A Qualitative Case Study. Issue 1 (June 2013) - Nazare, Suhas; Or, Calvin; Li, Kang; Xu, Jing
Attention has been given to the implementation failure of clinical information systems (CIS); however, the majority of previous investigations have been conducted in hospitals and clinics, rather than with a systems engineering perspective in long-term care and nursing home environments. In this present study, we examined the reasons behind a nursing home's abandonment of a CIS. Data were collected through field observations (n=12) and individual interviews (n=18) of CIS stakeholders in a nursing home in Hong Kong. Data were analyzed using the immersion/crystallization approach. A sociotechnical model (Sittig and Singh, 2010) was used to guide data extraction and analysis. Our findings showed that the observed implementation challenges were related to the eight dimensions of the sociotechnical model. Specific implementation challenges identified included system speed, accessibility, and stability; technical support; clinical content adequacy and availability; system usefulness and user interface design; computer literacy; familiarity with the system; experience in the health care profession; fit between the system, workflow and communication; inconsistency between workflow, work policy, and procedures; lack of financial support; conflict between government regulations and the functional needs of users; and lack of measurement and monitoring of system effectiveness.. The knowledge gained regarding these challenges improves prior understanding of CIS failure in nursing home settings. The results offer a knowledge base for possible solutions and strategies for further initiatives in CIS implementation.